The mitochondrial genome of the semi-slug Omalonyx unguis (Gastropoda: Succineidae) and the phylogenetic relationships within Stylommatophora - Guzmán, Leila Belén (2021)
Fil: Guzmán, Leila Belén. Universidad Nacional de Misiones. Instituto de Biología Subtropical; Argentina.